2017
DOI: 10.1016/j.aquaculture.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole reduces parasitic infection in juvenile pacu ( Piaractus mesopotamicus )

Abstract: Anthelmintic drugs are successfully used in aquaculture to control parasitic infections or infestations. This study analyzed the effectiveness of levamisole as an antiparasitic and its effect on the liver of juvenile pacu (Piaractus mesopotamicus). A total of 300 fish (180 ± 1.27 g; 16 ± 0.4 cm) were fed a diet containing levamisole hydrochloride (LHC) for fifteen days. A control group (T0) and four treatments were tested: T1 (100), T2 (150), T3 (300) and T4 (500) mg kg −1 LHC in quadruplicate (15 fish per rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
(56 reference statements)
1
18
0
Order By: Relevance
“…It has antiparasitic effect in production animals such as sheep [12], bovine [13], and also in the human species [14], paralyzing the muscles of the parasites in the host gastrointestinal tract [15]. Its antimicrobial effect on fish has been proven through the control of protozoa [16], nematodes [17,18], and bacteria [19]. In farmed fish, several studies demonstrate its immunostimulating effect, improving leukocyte production [20], respiratory burst activity [21], phagocytic activity [22,23], cytotoxic cell activity [24], oxidative radical production and serum myeloperoxidase [25], lysozyme [19,26,27], and complement system activity [19,21], although its mechanism of action is not known.…”
Section: Introductionmentioning
confidence: 99%
“…It has antiparasitic effect in production animals such as sheep [12], bovine [13], and also in the human species [14], paralyzing the muscles of the parasites in the host gastrointestinal tract [15]. Its antimicrobial effect on fish has been proven through the control of protozoa [16], nematodes [17,18], and bacteria [19]. In farmed fish, several studies demonstrate its immunostimulating effect, improving leukocyte production [20], respiratory burst activity [21], phagocytic activity [22,23], cytotoxic cell activity [24], oxidative radical production and serum myeloperoxidase [25], lysozyme [19,26,27], and complement system activity [19,21], although its mechanism of action is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary levamisole at the dose of 300 mg/kg dry diet has been reported to enhance Clarias fuscus fish resistance to pathogenic bacteria and markedly influence specific immunity system, while administration of levamisole at the dose of 600 mg/kg dry diet for 7 days resulted in immunosuppression of fish (Li et al, 2006). Feeding levamisole 300 mg/kg supplemented diet for 15 days was effective in controlling nematodal infection in juvenile paco ( Piaractus mesopotamicus ); however, the same protocol with the dose of 500 mg/kg feed resulted in pathologic changes in fish livers (Pahor‐Filho, Júnior, Pilarski, & Urbinati, 2017). Studies also suggested that antiparasitic activity of levamisole against amoebic gill disease of fish might be due to its immunomodulatory activity (Findlay, Zilberg, & Munday, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Levamisole is one of these anthelminthic drugs. This is an anthelmintic of imidazothiazole group that immobilizes parasites by causing muscle paralysis (HARTMANN, 1989;PAHOR-FILHO et al 2017). It has low toxicity towards fish in therapeutic baths (ALVES et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Levamisole can be delivered effectively via dietary supplementation, which would be much more feasible for industrial use, compared with injection and immersion baths (LI et al, 2006). Administration of levamisole in the dietary supplementation of fish may be an alternative for treatment against monogeneans, since this oral treatment can increase the deleterious effects on the parasites and increase the chances of fish survival (PAHOR-FILHO et al, 2017), especially when high concentrations of this anthelminthic drug are used. In addition, oral treatment eases the administration of the drug and there is no need to handle the fishes (TOJO & SANTAMARINA, 1998).…”
Section: Introductionmentioning
confidence: 99%